1960
DOI: 10.1901/jeab.1960.3-289
|View full text |Cite
|
Sign up to set email alerts
|

NOTE ON RESPONSE DIFFERENTIATION DURING A SIMPLE DISCRIMINATION1

Abstract: Apart from other requirements set by the experimenter, bar-pressing situations have at least one characteristic in common: the animal must learn how hard to press the bar if it is to procure reinforcement. (Notterman, 1959, has described the emission of forces over the course of operant level, CRF, and extinction.) This requirement is to be distinguished from additional demands placed upon the organism in the typical experiment involving discrimination of exteroceptive stimuli. In the latter instance, and in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1963
1963
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…(The top frame is mean response rate, the middle is mean first response duration, and the bottom represents the mean duration of all responses under the two stimulus conditions.) Herrick, 1963;Notterman & Block, 1960). The gradual, but monotonic, decrease in the reinforced duration replicates Margulies' (1961) results for duration under regular reinforcement.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…(The top frame is mean response rate, the middle is mean first response duration, and the bottom represents the mean duration of all responses under the two stimulus conditions.) Herrick, 1963;Notterman & Block, 1960). The gradual, but monotonic, decrease in the reinforced duration replicates Margulies' (1961) results for duration under regular reinforcement.…”
Section: Resultssupporting
confidence: 81%
“…For example, S 4 response amplitudes are greater (Burke, 1963) and more variable (Herrick, 1963) than S D amplitudes. Similar patterns are evident in duration measures and force indexes (Notterman & Block, 1960). Interestingly, these effects persist throughout training.…”
Section: Discussionsupporting
confidence: 68%
“…DISCUSSION The results summarized in Table 3 and Figure 1 confirm the linear system theory's third prediction concerning k-namely, that the rate of change of k over a given magnitude range varies directly with the force requirement on the operandum. The existing literature on response force (e.g., Notterman, 1959;Notterman & Block, 1960;Notterman & Mintz, 1962) does not address this rate-of-change effect. However, Chung (1965) found that the absolute rate of pigeon's key pecking on single-alternative VI schedules was a decreasing function of the force requirement on the key.…”
Section: Resultsmentioning
confidence: 99%
“…But response magnitude is easily affected by the topography of the unconditioned response (Allan, 1992;Ploog & Zeigler, 1996). There are instances in which, even when contingencies are held constant, response force may covary negatively with other measures of strength (Amsel, 1962;Logan, 1956;Notterman & Block, 1960;Svartdal, 1993).…”
Section: The Properties Of a Responsementioning
confidence: 99%